Perancangan Sistem Informasi Perhotelan Pada Hotel Perdana Kabupaten Pulau Morotai - Papuangan, Miswar; Suparmanto, Agus; Lule, Alwadud (Madani: Jurnal Ilmiah Multidisiplin, 2024)
The Perdana Hotel is one of the hotels in Morotai Island Regency which is developing and continues to strive to improve service and hotel quality standards from various aspects, including the aspect of utilizing information technology. Rental of rooms in prime hotels is still done by recording them in the reservation book, so the room rental system needs to be improved in line with current developments in information technology. Several systems that need to be developed are room rental booking systems, check-in and check-out. The aim of this research is to design a website-based information system that can help parties manage the room rental system more efficiently. The system testing method designed uses white box testing. White box testing allows the test case designer to gain a measure of the logical complexity of the procedural design and use the measure as a guide to the basis set of the work path. The results of the system design and testing that have been carried out can help hotels manage room reservation data by customers easily and efficiently without having to come directly to the hotel.